he Vaishedika Atomism - A key to all philosophical quests, related to cosmology. - Muhunthan, S. (University of Jaffna, 2015)
Vaishedika is one out of the Six Darshanas which are the most important among the Indian schools of Philosophy. Though this is one of the Orthodox School of Thought in India it is deeply concerned with physical nature, more than any other metaphysical quests. Thus Vaishedika with the help of the two theories, viz; Theory of substance and atomism, has deeply gone into the study of the Universal phenomenon. The important interpretation behind Vaishedika is the justification that all structural forms within universal phenomena are created by the compounding and separation of atoms. Comparatively, though Vaishedika was contemporary to Greek and Jain atomic theories, it has certain unique qualities of its own.
Keywords: Atomism; cosmology; Pluralistic; Realism